NO TITLE FOUNDNO TITLE FOUND. Issue 2 (1st October 2020) - Wade, Cameron
#UsToo debuted at the 39th Annual Conference of the North American Drama Therapy Association. It was written and performed by the author as an autoethnographic therapeutic theatre performance investigating her experiences with sexual assault and harassment perpetrated by members of the drama therapy community. This article includes an annotated version of the script with a discussion on form, content, aesthetic choices and embodiment. This article concludes with a synthesis of authorial learnings and outcomes throughout the devising, rehearsal and performance processes.